2008
DOI: 10.1038/eye.2008.325
|View full text |Cite
|
Sign up to set email alerts
|

Subjective visual perceptions during vitreoretinal surgery under local anaesthesia

Abstract: Purpose To evaluate the visual experiences of patients during vitreoretinal surgery under local anaesthesia (LA). Methods Prospective questionnaire survey of 80 patients within 30 min of completion of vitreoretinal surgery under LA. Preoperative visual acuity, surgical procedure and its duration, efficacy of the local block, as well as intraoperative perceptions of flashes, colours, movements, and seeing instruments were documented. Results A sub-Tenon's block was performed in 62/80 (77.5%) and a peribulbar bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…2,3 The variation in the proportion of patients frightened is similar to that described during cataract surgery, which ranges from 3 to 19.4%. 4 There are many possible reasons for this variation between studies, including cultural differences, as well as the previous operative experience of the patients. In the cohort of 65 patients described by Tan et al, 2 61 (93.8%) were undergoing vitreoretinal surgery for the first time.…”
Section: Richardson and H Watermanmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 The variation in the proportion of patients frightened is similar to that described during cataract surgery, which ranges from 3 to 19.4%. 4 There are many possible reasons for this variation between studies, including cultural differences, as well as the previous operative experience of the patients. In the cohort of 65 patients described by Tan et al, 2 61 (93.8%) were undergoing vitreoretinal surgery for the first time.…”
Section: Richardson and H Watermanmentioning
confidence: 99%
“…It has been suggested that previous ocular surgery may serve as a 'practical' form of counselling on the range of possible intraoperative visual experiences. 4 A study on patients undergoing cataract surgery 5 reported that 15.8% of patients undergoing surgery for the first time were frightened by their intraoperative visual sensations, compared with only 6% for those having surgery to the second eye.…”
Section: Richardson and H Watermanmentioning
confidence: 99%
See 1 more Smart Citation
“…We agree that there is a variation in the number of patients who are frightened by intra-operative VPs, but overall the percentage of such patients is small. It is appropriate to state that the majority of patients find VPs during intra-ocular surgery bearable; some find them even pleasant [2][3][4] and one has found them good enough to write a poem about them. 5 In our study, 52/72 (72.22%) of patients described their VPs as 'bearable', and only two patients (2.7%) thought that they were 'frightening'.…”
Section: Reply To Dr Tanmentioning
confidence: 99%
“…3 Indeed, some authors are even using IVT therapeutic agents for relatively rare disorders, such as central serous chorioretinopathy. 3 Patients' visual perceptions and experiences induced by frequently performed ophthalmic surgical procedures, such as cataract surgery (under topical [10][11][12][13][14][15] and regional anesthesia [11][12][13][14]16,17 ), glaucoma filtration surgery, 18 and vitreoretinal surgery, [19][20][21][22] are well documented. Indeed, the beneficial effect of preoperative counseling with respect to known and anticipated visual experiences during phacoemulsification cataract surgery, under topical anesthesia, in terms of reducing patients' fear, has been described.…”
Section: Introductionmentioning
confidence: 99%